2019
DOI: 10.15294/sji.v6i2.19503
|View full text |Cite
|
Sign up to set email alerts
|

Face Identification Based on K-Nearest Neighbor

Abstract: Face identification has been widely applied this time, such as security on gadgets, smart home security, and others. Face dominates as a biometric which is most increase in the next few years. Face is used for biometric identification which is considered successful among several other types of biometrics and accurate results. Face recognition utilizes facial features for security purposes. The classification method in this paper is K-nearest Neighbor (KNN). The K-Nearest Neighbor algorithm uses neighborhood cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 7 publications
0
17
0
4
Order By: Relevance
“…KNN can give results with great accuracy, according to a number of earlier research. For instance, research on face categorization using KNN yields an accuracy of 81 percent when k = 1 (Wirdiani et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…KNN can give results with great accuracy, according to a number of earlier research. For instance, research on face categorization using KNN yields an accuracy of 81 percent when k = 1 (Wirdiani et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several previous studies have shown that KNN can produce high accuracy. Such as research on face classification with KNN which produces an accuracy of 81% with k = 1 (Wirdiani et al, 2019). Furthermore, research on the classification of tomato maturity using K-Nearest Neighbor which produces the highest level of accuracy reaches 92.5% with the k parameter used as many as 3 (Sanjaya, Pura, Gusti, Yanto, & Syafria, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…One of the simple algorithms that can be used in the classification process to match data between testing and training data from face datasets is KNN [9]. KNN was used in the early 1970s for statistical estimation and pattern recognition [22].…”
Section: Classification With Knn Algorithmmentioning
confidence: 99%
“…Classification using KNN can be done after feature extraction to identify face. As in Wirdiani et al [9] carried out three stages to identify face including face detection, feature extraction and classification. The method used to extract features is principal component analysis (PCA) and the method to perform classification is k-nearest neighbor (KNN).…”
Section: Introductionmentioning
confidence: 99%